Evaluation of Oxidative Stress in Molecular Diagnostic Patients with Toxoplasma gondii in A Najaf province - Huda Radhi jabr; Fatima Fairs Mailk; Muntazer Muhammad Ibrahim; Zahraa Sajed Hussien; Rasha Amer Nouri Al-Tufaili (Genius Journals, 2023)
Toxoplasmosis is caused by infection with Toxoplasma gondii. This coccidian protozoan is normally transmitted to humans by ingestion of either oocysts from cat feces, or by tissue cysts in raw or undercooked meat It is one of the most important problems in immunocompromised individuals. The frequency of primary maternal toxoplasma infection depends on the proportion of seronegative pregnant women who are susceptible to infection and on the prevailing infection risk. In the study you mentioned, the researchers likely used molecular diagnostic techniques to evaluate the presence of T. gondii in patients in Najaf province. They may have also assessed oxidative stress in these patients, which is a type of cellular damage caused by the production of reactive oxygen species (ROS). Elevated levels of ROS can cause damage to DNA, proteins, and lipids, and may be associated with the development of various diseases. The researchers may have measured markers of oxidative stress, such as certain enzymes or biomolecules, in order to understand the potential relationship between T. gondii infection and oxidative stress
Keywords: Toxoplasmosis; Toxoplasma gondii; Coccidian protozoan; Oxidative stress